A new species of Amolops (Anura: Ranidae) from southern China - Sung, Yik-Hei; Hu, Ping; Wang, Jian; Liu, Hai-Jun; Wang, Ying-Yong (Zootaxa, 2016)
A new species, Amolops albispinus sp. nov. is described based on a series of specimens collected from Mt. Wutong, Shenzhen, Guangdong Province, China. The new species can be distinguished from other known congeners by molecular divergence in the mitochondrial COI and 16S rRNA gene and morphological characters including presence of white conical spines on the lips, loreal and temporal regions, excluding the tympanum; small body, SVL 36.7–42.4 mm in adult males and 43.1–51.9 mm in adult females; very rough dorsal skin of body with numerous raised large warts; olive-brown dorsum with dark brown blotches; strongly developed vomerine teeth; absence of vocal sacs; absence of tarsal glands; absence of dorsolateral folds; presence of circummarginals groove on the disk of first finger; and absence of outer metatarsal tubercles. At present, the genus Amolops contains 51 species, of which 23 occur in China.